Management of wireless home networking technologies in the context of composite radio environments. - Demestichas, P. (Mobile computing and communications review.)
BRAN/WLAN systems are seen as promising solutions for covering residential, business, etc., environments, and therefore realising the wireless home/office concept. This paper presents management functionality for augmenting the exploitation of these systems, by making feasible their integration in a composite radio (CR) context. In the followed approach the first point will be to revisit the main features of a HiperLAN2 system. Next, will be the presentation of a general Service and Network Management System (SNMS) architecture. The last point will be the functionality of the SNMS components that are tailored to the managed HiperLAN2 technology. A set of resource management problems will be addressed, for exploiting HiperLAN2 networks in a CR context.